Racism in Agent Societies: A Model Based on the Concept of Capability-Based Social Control Mechanism - Costa, Antônio Carlos da Rocha (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2021)
This paper builds both on S. Haslanger’s conceptions of ideology and racism, and on Carmichael & Hamilton typology of racism, to formally introduce a model for racism in agent societies. Racism is modeled as a system of racist capability-based social control mechanisms, each composed of practices, attitudes, meanings, and material and power conditions that a variety of social groups adopt and handle, regarding some particular set of social groups, to the effect of disempowering the members of the latter groups, on the basis of racist criteria, with respect to the possibility of their participation in some part of the organization and functioning of the agent society they inhabit. Two main forms of racism are considered: overt racism and institutional (or structural, or systemic) racism. A case study formally models the racist foundation of the religious system of prototypical Brazilian colonial plantations.